Pelatihan Break Even Point Analysis Sebagai Alat Perencanaan Laba Bagi Pelaku Usaha Pemula: Strategi Keuangan Menghadapi Masa Pandemi Covid-19 - Anita Erari; Aprianto La’lang Kuddy (Cenderabakti: Jurnal Pengabdian Kepada Masyarakat, 2022)
This Community Service activity aims to improve the knowledge and skills of startup entrepreneurs in Jayapura City in using Break Even Point Analysis as a model/tool for good business profit planning, as well as to increase interest in entrepreneurship and the ability to manage and control company finances for entrepreneurs. Beginner business actors in Jayapura City by utilizing Break Even Point Analysis. This activity has a positive impact on the participants of the activity. The result of this activity is an increase in participants' understanding of the BEP analysis. Through this BEP analysis, participants can find out basic calculations in assessing the condition of a business, especially in running an entrepreneurial business that they are working on as beginners during the Covid-19 pandemic.